Use of colored agrotextiles and length of stay in the cultivation of yellow melons (Research, Society and Development, 2021)
The coverage of plants with agrotextiles of different colors and length of stay may influence the productivity of the crop. The objective of this study was to evaluate the influence of the use of colored agrotextiles and their length of stay on the cultivation of melon plants in the conditions of the semiarid region of Paraíba. The experiment was fulfilled out at the Experimental Farm of the Federal University of Campina Grande, located in the municipality of São Domingos – PB.  The treatments were distributed in a randomized block design in a 4 x 4 factorial scheme, with four repetitions and consisting of four colors of agrotextile (orange, white, gray, and blue) and four lengths of stay (15, 18, 21, and 24 days after transplanting).  The following characteristics were evaluated: active photosynthetic radiation, average temperature, number of fruits per plant, average fruit mass and total productivity. The use of colored agrotextiles associated with the length of stay promoted a change in the production characteristics of the yellow melon fruits. The highest productivity, number of fruits, and mass of the melon fruits were obtained when the plants were covered with the orange-colored agrotextile at 15, 18, and 24 days after transplantation, respectively. The long stay of the agrotextile affected the content of total soluble solids.